Reações multicomponentes de Diels-Alder com parabenzoquinonas : intermediários para Sesquiterpenos Eudesmanos - Vieira, Ygor Willian (2010)
In the first part of this thesis we describe the study of the oxidation of phenols to p-benzoquinones. The metal complexes used as catalysts in this study are: [CoII(salen)], [CoII(dmsalen)], [CoII(salpn)], [CoII(dmsalpn)], [CuII(salen)], [NiII(salen)] and [VOIV(salen)]. The oxidation with [CoII(salen)] showed better results, oxidizing ten of the eleven phenols employed. We also employed other oxidants such as hydrogen peroxide (H2O2 30%), OXONE®, dimethyl dioxirane (DMD) and iodoxybenzoic acid (IBX), however, OXONE® and DMD oxidized only the alkyl disubstituted phenols. In the second part, we studied the optimization of the Diels-Alder reaction in multicomponent version (MCR) with p-benzoquinones, as well as the scalingup of these reactions. We also tested this methodology (Diels-Alder/MCR) under microwave irradiation (Scheme 1). The Diels-Alder reactions in the multicomponent version conducted under reflux conditions showed yields in the range of 60-70%. This range was kept up even in the scale up of these reactions to 100 mmol. When these reactions were conducted under microwave irradiation, the yields were obtained in the range of 30-40%. In this case the reactions were conducted in the absence of solvents and was observed a decrease of the reaction time from 24 hours to 30 minutes. A theoretical study of the Diels-Alder reaction was conducted through computer calculations of the frontier molecular orbital energies (HOMO and LUMO), in order to explain the reactivity of diene-dienophiles pairs. Through these calculations we can conclude that the greater the number of alkyl groups attached to double bonds of the dienophile, the lower the reactivity of it face to the Diels-Alder reaction in the normal electron demand. In the case of the dienes it was found by the calculations that the benzamide substituent group is a better activating group to the diene than the acetamide group. Alkyl groups as substituents on the terminal carbon increases the HOMO energy.